Analyzing the Effect of Using the Geoboard for Learning the Pythagorean Theorem (Unnes Journal of Mathematics Education, 2022)
This research considered the need to implement didactic materials during learning the Pythagorean theorem as one of the topics present in mathematics curricula around the world. The objective was to analyze the effect of the use of the geoboard in the learning of the Pythagorean theorem with high school students. The contributions of the theory of figurative concepts and concrete didactic materials were considered. The method used was a case study design by applying a task with concrete material with ten students. Among the main results, the construction of figures on the geoboard was obtained by analyzing the students' mental images. It was also possible to demonstrate visual skills and reasoning development when implementing this material. In conclusion, the effect of use of the geoboard in the study of the Pythagorean theorem allowed the recognition of the difference in the unit of measurement between the legs and the hypotenuse. Also, the development of the skills allowed the students to build the concept of the relationship between the figures built within the square of the hypotenuse with the area of the squares corresponding to the legs.